Stepwise radical cation Diels–Alder reaction via multiple pathways - Shimizu, Ryo; Okada, Yohei; Chiba, Kazuhiro (Beilstein Journal of Organic Chemistry, 2018)
Herein we disclose the radical cation Diels–Alder reaction of aryl vinyl ethers by electrocatalysis, which is triggered by an oxidative SET process. The reaction clearly proceeds in a stepwise fashion, which is a rare mechanism in this class. We also found that two distinctive pathways, including “direct” and “indirect”, are possible to construct the Diels–Alder adduct.
Keywords: Diels–Alder reaction; radical cation; rearrangement; single electron transfer; stepwise

(untitled) - Twilton, J.; Le, C.; Zhang, P.; Shaw, M. H.; Evans, R. W.; MacMillan, D. W. C. (Nat. Rev. Chem., 2017)

(untitled) - Prier, C. K.; Rankic, D. A.; MacMillan, D. W. C. (Chem. Rev., 2013)

(untitled) - Skubi, K. L.; Blum, T. R.; Yoon, T. P. (Chem. Rev., 2016)

(untitled) - Schultz, D. M.; Yoon, T. P. (Science, 2014)

(untitled) - Kärkäs, M. D.; Porco, J. A., Jr; Stephenson, C. R. J. (Chem. Rev., 2016)

(untitled) - Narayanam, J. M. R.; Stephenson, C. R. J. (Chem. Soc. Rev., 2011)

(untitled) - Yoshida, J.-i.; Shimizu, A.; Hayashi, R. (Chem. Rev., 2018)

(untitled) - Yoshida, J.-i.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Yan, M.; Kawamata, Y.; Baran, P. S. (Chem. Rev., 2017)

(untitled) - Horn, E. J.; Rosen, B. R.; Baran, P. S. (ACS Cent. Sci., 2016)

(untitled) - Francke, R.; Little, R. D. (Chem. Soc. Rev., 2014)

(untitled) - Sperry, J. B.; Wright, D. L. (Chem. Soc. Rev., 2006)

(untitled) - Feng, R.; Smith, J. A.; Moeller, K. D. (Acc. Chem. Res., 2017)

(untitled) - Moeller, K. D. (Synlett, 2009)

(untitled) - Tang, F.; Moeller, K. D. (Tetrahedron, 2009)

(untitled) - Reynolds, D. W.; Bauld, N. L. (Tetrahedron, 1986)

(untitled) - Lin, S.; Ischay, M. A.; Fry, C. G.; Yoon, T. P. (J. Am. Chem. Soc., 2011)

(untitled) - Stevenson, S. M.; Shores, M. P.; Ferreira, E. M. (Angew. Chem., Int. Ed., 2015)

(untitled) - Higgins, R. F.; Fatur, S. M.; Shepard, S. G.; Stevenson, S. M.; Boston, D. J.; Ferreira, E. M.; Damrauer, N. H.; Rappé, A. K.; Shores, M. P. (J. Am. Chem. Soc., 2016)

(untitled) - Reynolds, D. W.; Harirchian, B.; Chiou, H. S.; Marsh, B. K.; Bauld, N. L. (J. Phys. Org. Chem., 1989)

(untitled) - Pabon, R. A.; Bellville, D. J.; Bauld, N. L. (J. Am. Chem. Soc., 1984)

(untitled) - Harirchian, B.; Bauld, N. L. (J. Am. Chem. Soc., 1989)

(untitled) - Aplin, J. T.; Bauld, N. L. (J. Chem. Soc., Perkin Trans. 2, 1997)

(untitled) - Harirchian, B.; Bauld, N. L. (Tetrahedron Lett., 1987)

(untitled) - Lin, S.; Lies, S. D.; Gravatt, C. S.; Yoon, T. P. (Org. Lett., 2017)

(untitled) - Okada, Y.; Chiba, K. (Chem. Rev., 2018)

(untitled) - Yamaguchi, Y.; Okada, Y.; Chiba, K. (J. Org. Chem., 2013)

(untitled) - Okada, Y.; Nishimoto, A.; Akaba, R.; Chiba, K. (J. Org. Chem., 2011)

(untitled) - Okada, Y.; Chiba, K. (Electrochim. Acta, 2011)

(untitled) - Okada, Y.; Akaba, R.; Chiba, K. (Org. Lett., 2009)

(untitled) - Arata, M.; Miura, T.; Chiba, K. (Org. Lett., 2007)

(untitled) - Chiba, K.; Miura, T.; Kim, S.; Kitano, Y.; Tada, M. (J. Am. Chem. Soc., 2001)

(untitled) - Imada, Y.; Yamaguchi, Y.; Shida, N.; Okada, Y.; Chiba, K. (Chem. Commun., 2017)

(untitled) - Okada, Y.; Yamaguchi, Y.; Ozaki, A.; Chiba, K. (Chem. Sci., 2016)